Pengembangan e-LKPD Berdiferensiasi Terintegrasi HOTS Melalui Kecerdasan Majemuk Untuk Meningkatkan Kemampuan Berpikir Sistem - Hanna Benedicta Simanjuntak; Dewi Lengkana; Tri Jalmo; Abdurrahman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop differentiated electronic student worksheets (e-LKPD) integrated with Higher-Order Thinking Skills (HOTS) and multiple intelligences that are valid, practical, and effective in enhancing students’ systems thinking skills. The research follows the Borg and Gall R&D model. The study population comprised eighth-grade students from SMPN 1 Mesuji in the 2024/2025 academic year. A purposive sampling technique was employed to assign class VIIIA as the experimental group and class VIIIB as the control group. Data collection instruments included need analysis questionnaires, expert validation forms, student and teacher response questionnaires, pretest and posttest items, reflection sheets, and learning implementation observation sheets. Data analysis was conducted using independent sample t-tests on n-Gain scores. The findings revealed that: (1) the e-LKPD was rated as highly valid (95%) by expert reviewers; (2) it was considered highly practical by students (95%) and teachers (100%); (3) it was effective in improving systems thinking skills with a high n-Gain score (0.75) and a large effect size (0.95); and (4) it achieved a very high implementation level (87.19%). These results indicate that the developed e-LKPD is suitable for use in science learning, particularly on the topic of the digestive system, to enhance students' systems thinking skills.